A systematic mapping protocol of methods and practices employed in ecological niche modelling of anthrax - Gachohi, John; Bett, Bernard; Karanja, Simon; Kikuvi, Gideon; Nyamai, Mutono; Mwangi, Thumbi; Njenga, Kariuki (Global Epidemiology, 2019)
AbstractBackgroundDemand for policy-relevant solutions focused on spatially-targeted strategies for prevention and control of diseases is growing. This demand can, in part, be fulfilled through predicting the distribution of environments and geographies that support occurrence of disease or disease-causing pathogens, a task ecological niche modelling (ENM) effectively accomplishes. Bacillus anthracis, the causative agent of the high-impact zoonoses anthrax is a classic exemplar of an environmentally-borne pathogen whose distribution (and that of anthrax) has been predicted via ENM. In developing credible niche models, modellers pursue certain practices and procedures to answer diverse research questions relevant to anthrax ecology. At the same time, recommendations have been made that niche models be interrogated appropriately to provide answers to specific challenges encountered regarding best methods and practices. Specifically, the objective of this protocol is to describe a plan for characterizing input data, algorithms, model assessment approaches and model practical applications employed in ENM for anthrax to finally generate a systematic map for this information. DesignWe will potentially review all relevant studies that describe anthrax ENMs across the globe. We will exhaustively search for these studies in a hierarchical approach by screening titles, abstracts and full texts using a set selection criterion from two databases – PubMed and Web of Science. We will then design and populate a database with metadata specific to input data, algorithms, model assessment approaches and model practical applications from the reviewed models and present the database in form of a systematic map. Using a procedure termed “coding”, we will designate variables to each model for a set of relevant attributes of each of these four topics. The systematic map will be an accessible descriptive narrative assessment of the state of knowledge on anthrax ENM practices and procedures across the globe.